Characterization of PVDF hollow fiber membrane - Lau, Xiang Ling. (2009)
Physical properties of the membranes are the keys to the greater performance of the membrane. Fabrication parameters and conditions were factors to affecting the characteristic of the membrane. In this report, post treatment annealing temperature, variation of fabricating conditions together with additional additives to the membranes were investigated. Two fabrication techniques - Non-Solvent Induced Phase Separation (NIPS) and Thermal Induced Phase Separation (TIPS) were exploited for membranes fabrications. Five tests were carried out on NIPS and TIPS membranes to better understand selectivity, permeability and crystallization morphology of the PVDF membranes.